The magician a novel - Tóibín, Colm 1955- (Scribner, 2021)
"The Magician opens at the turn of the twentieth century in a provincial German city where the young boy, Thomas Mann, grows up with a conservative, conventional father and a Brazilian mother, exotic and unpredictable, who will never fit in. He hides both his artistic aspirations and his homosexual desires from this father, and his sexuality from everyone. He longs for the charismatic, beautiful, rich, cultured young Jewish man, but marries his twin sister. He longs for a boy he sees on a beach in Venice and writes a novel about him. He has six children. He is the most successful novelist of his time. He wins the Nobel Prize and is expected to lead the condemnation of Hitler. His oldest daughter and son share lovers. They are leaders of Bohemianism and of the anti-Nazi movement. This stunning combination of German propriety and Bohemian revolution goes hand in hand for decades. We see the rise of Hitler, the forced exile of a swath of German writers and artists, Mann's narrow escape to America, his sojourn at Princeton, along with fellow exile Einstein, and his final move to LA in the late 40s where he presided over an astonishing community of writers, artists and musicians, including Brecht and Shoenberg, even as his children court tragedy. To call this a portrait of an artist is both reductive and true-it is a novel about a character and a family, fiercely engaged by the world, profoundly flawed, and as flamboyant as it's possible to be"--
Keywords: Mann, Thomas -- 1875-1955; Mann, Thomas / 1875-1955 / Fiction; Novelists, German / Fiction; Gay men / Fiction; Bohemianism / Fiction; Germany / History / 1871- / Fiction; Los Angeles (Calif.) / Fiction; United States / History / 1945- / Fiction; FICTION / Literary; FICTION / Historical / General; FICTION / Biographical; Mann, Thomas / 1875-1955; Bohemianism; Gay men; Novelists, German; California / Los Angeles; Germany; United States; Since 1871; Biographical fiction; Fiction; Historical fiction; History; Novels; Fiktionale Darstellung